Etika dalam Komunikasi Islam - Muhardisyah Muhardisyah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2017)
Ethics Communication in the Islamic perspective is the rule of human behavior in keeping its verbal from words that are not meaningful and will bring harm to him in the world and the hereafter. Ethics in Islam has a very deep rule, then it becomes a sacred and indisputable ethic. The content of the Qur'an contains a moral appeal aimed at organizing the social order to be more civilized and more awake. There are examples of good communication in al-Qur'an such as, Quaulan Principle of Balighan, Principles of Qaulan Kariman, Principles of Qaulan Maysuran, Principles of Qaulan Ma'rufan, Principles of Layorial Qaulan and Qaulan Sadidan Principles. This shows that Islam maintains a communication for the sake of a peaceful and tranquil life.